Asuhan Kebidanan Continuity of Care (COC) pada Ny. S Umur 32 Tahun di Susukan Ungaran Timur - Istatik Ulyanita; Ari Widyaningsih (Universitas Ngudi Waluyo, 2024)
Most maternal deaths are caused by obstetric complications around childbirth. One effort to reduce maternal mortality rate is through the implementation of the Continuity of Care (COC) program. This program is a comprehensive and coordinated consultation and coaching program for pregnant women until delivery in the form of a partnership between families with students, midwives, and lecturers in order to contribute to efforts to reduce maternal mortality rate and infant mortality rate. Based on this description, the author is interested in conducting